Demographic Associations of Diabetes Status by Both Fasting Plasma Glucose Concentration and Glycated Hemoglobin in a Community Survey in Galle District, Sri Lanka - Keddagoda Gamage Piyumi Wasana; Anoja Priyadarshani Attanayake; Thilak Priyantha Weerarathna; Kamani Ayoma Perera Wijewardana Jayatilaka (Journal of Nutrition and Metabolism)
Diagnostic tools used in detecting individuals with diabetes mellitus (DM) include fasting plasma glucose (FPG), glycated hemoglobin (HbA1C), and oral glucose tolerance test (OGTT). The present study was aimed to determine the demographic associations of diabetes status by both tests (FPG and HbA1C) in Galle district, Sri Lanka. 147 adults (30–60 years) who are having FPG ≥ 126 mg/dL underwent demographic evaluations and testing for HbA1C. Group 01 (diabetes status diagnosed by both tests) and group 2 (diabetes status diagnosed only by FPG) were compared using independant sample t-test and chi-square test. Logistic regression was used to study the association between the demographic factors and the diabetes status by both tests. Of the 147 study subjects, 38.1% were males, 61.9% were females, and 63.3% had a family history of diabetes among first-degree relatives (FDR). Mean age, body mass index (BMI), waist circumference (WC), FPG, and HbA1C of the participants were 48.4 ± 7.2 years, 25.1 ± 4.0 kg/m2, 88.8 ± 9.0 cm, 139.4 ± 30.1 mg/dL, and 6.4 ± 0.7%, respectively. The prevalence of diabetes based on both tests was 55.1%. There is a significant difference in mean BMI and WC while no significant differences in mean age between groups 01 and 02. No association was seen between gender and diabetes status (X2(1) = 0.086, p=0.770), while a significant difference was observed between DM among FDR and diabetes status (X2(1) = 33.215, p<0.001). Significance of odds of having diabetes by both tests with rising BMI (OR = 1.97, CI 1.15–3.36, p=0.013) and DM among FDR (OR = 7.95, CI 3.54–17.88, p=0.000) was seen. We conclude rising BMI and having DM among FDR are strongly associated with diabetes status diagnosed by both tests of FPG and HbA1C in community screening.